Hepatitis B vaccination coverage among cleaning staffs in a government tertiary care centre in mid-Kerala - Tomson, Richard; N., Rithu; K. V., Jaya; A. P., Sandra; Vallil, Rifna Sherin; Latif, Roshan; V. S., Sameera; Velayudhan, Sandra K.; Kurup, Shamkrishna H.; C. P., Shahin Ahamed; Amina, Rinsha; V., Sona; et al. (International Journal Of Community Medicine And Public Health, 2024)
Background: Hepatitis B virus (HBV) could be responsible for acute and/or chronic pathology in liver. Since, contact with body fluids of infected or needle prick from syringe used on an infected is the principal mode of transmission of hepatitis B infection, health care workers (HCWs) constitute the high-risk group. In this study, we wanted to estimate hepatitis B vaccination coverage among cleaning staffs of government tertiary care centre in mid-Kerala. For effective intervention, it is essential to know the factors responsible for accepting the vaccination as well as for refusal and incomplete immunization. The objective was to find out hepatitis B vaccination status and the reason for not taking hepatitis B vaccine among cleaning staff in Government Medical College Thrissur. Methods: Cross sectional study was conducted among 184 cleaning staff and attenders which include grade 2 staff, dhobis, Kudumbashree workers and part time cleaners of government tertiary care centre in mid-Kerala through telephonic interview using semi structured questionnaire. Results: Among the 184 study subjects, 57.61% were vaccinated against hepatitis B. Out of the 83 cleaning staffs who were vaccinated only 53.01% is completely vaccinated with 3 doses of vaccine (fully vaccinated). 46.99% of vaccinated staffs took either one or two doses, that is partially vaccinated. Out of the non-vaccinated study subjects, most common reason (39.62%) for not taking the vaccine was lack of awareness about the vaccine. Conclusions: From this study it was found that majority of the cleaning staff were not aware about hepatitis B infection and vaccination available for it.